Adaptive fuzzy output-feedback control for a class of nonlinear pure-feedback systems with time delays. Issue 6 (26th April 2017) - Wang, Honghong; Chen, Bing; Lin, Chong; Sun, Yumei
ABSTRACT: This paper investigates observer-based adaptive fuzzy control for a class of delayed nonlinear systems in pure-feedback form. We first proposed a linear observer to get the estimation of the system's state. And then utilise fuzzy logic systems to model those nonlinearities. Further, adaptive fuzzy approach and backstepping technique are combined to develop the desired controller via Lyapunov analysis. The suggested adaptive fuzzy control scheme ensures that all the signals of the resulting nonlinear system converge to a small neighbourhood of the origin. Then a real simulation is used to illustrated the effectiveness of our results.